Housing Relocation Policy and Violence: A Literature Review. (December 2016) - Casas, Andrea; Duell, Jessica; O'Malley, Teagen; Documet, Patricia; Garland, Richard; Albert, Steven; Fabio, Anthony
This article summarizes and reviews the cross-discipline literature on violent crime in destination neighborhoods postrelocation in order to build a more comprehensive picture of risk factors for violence, as well as how and why housing policies influence risk of violence. High rates of violent crime continue to be a persistent problem in areas of concentrated poverty and public housing. Modern housing programs such as Moving to Opportunity and Housing Opportunities for People Everywhere are popular interventions for reducing the density of low-income people receiving public housing assistance by relocating residents of distressed housing projects. However, evidence suggests that relocated residents may not experience less violence or improved safety in their new communities.